SECURITY INFORMATION SYSTEM OF THE COMPUTER CENTER IN MU’TAH UNIVERSITY - Alnawaiseh, Asma Jmeel (European Scientific Journal, ESJ, 2014)
The aim of this paper is to study the importance of security and protection at the computer center of Mu’tah University. In this study, we analyzed the following questions: Is security and protection a necessary requirement? What is the role management has applied to secure systems? What are the factors that have affected the security of any system? Finally, how can I secure my system after building it, and what methods can I use? Therefore, the data for this paper collected from the questionnaire was designed to achieve the stated objectives, and to encourage high response rate based on the questionnaire presented in international journals found on websites. As for the structured interview, it was used to enrich the data collected by the researcher.